Oral manifestations of dengue virus infection: a scoping review for clinical dental practice - Lucas Peixoto de Araújo; Stefan Kickhofel Weisshahn; Eduarda Thome do Carmo; Bruna Cavalcante Chaves; Mateus de Azevedo Kinalski; Nícolas Kickhofel Weisshahn; Sarah Arangurem Karam (BMC Oral Health)
Abstract Background Dengue virus (DENV) infection, a mosquito-borne disease, presents a significant public health challenge globally, with diverse clinical manifestations. Although oral dengue manifestations are uncommon, they can serve as crucial diagnostic indicators and impact patient management in dental practice. This scoping review aims to map the evidence on the oral manifestations associated with DENV infection and their clinical implications for dental practice. Methods This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines and was registered on PROSPERO (CRD42022337572). A comprehensive search was conducted across six electronic databases (MEDLINE, Web of Science, Scopus, Embase, Cochrane Library, and LILACS/BBO) up to June 2024. Eligible studies included case reports, case-control, cohort, and cross-sectional studies reporting oral manifestations in patients with DENV infection. Results A total of 41 studies were included, comprising 17 case reports, 15 retrospective cohort studies, 4 prospective cohort studies, and 5 cross-sectional studies. Gingival bleeding, oral ulceration, bilateral inflammatory increase in the parotid glands, and lingual hematoma were the most frequently reported oral manifestations. Less common manifestations included Ludwig’s angina, osteonecrosis of the jaw, and angular cheilitis. These findings suggest a broad spectrum of oral symptoms that could aid in the early identification and management of dengue patients. Conclusions This review highlights the importance of recognizing oral manifestations in dengue patients, which can facilitate early diagnosis and intervention, particularly in dengue-endemic regions. Dental professionals play a crucial role in identifying these symptoms and improving patient outcomes. Further research is needed to explore the pathophysiological mechanisms underlying these manifestations and to develop standardized protocols for clinical assessment and management. Clinical relevance This paper highlights the role of dental professionals in early dengue diagnosis, emphasizing oral manifestations like gingival bleeding. It promotes interdisciplinary care, improving patient outcomes and management in dengue-endemic regions.